Weneckie miejsca wyobraźni. Fondamenta degli Incurabili – próba interpretacji - Siemońska, Olga (Studia Rossica Posnaniensia, 2022)
The purpose of this article is to reflect on the phenomenon of travel to the places in Venice associated with the Russian poet Iosif Brodsky and the way in which the Fondamenta degli Icurabili, a place of imagination that is the title of the Russian and Italian-language translation of the essay Watermark, functions in space and consciousness of travellers. The article focuses primarily on individual literary journeys that were reflected in or even inspired the traveller’s writing activities. The experiences of being in the Fondamenta degli Incurabili and trying to understand the meaning of the toponym were described by many authors of contemporary non-fiction texts about Venice: Yuri Lepski, Yelena Yakovich, Gleb Smirnov, Arkady Ippolitov, Ekaterina Margolis. Two texts are particularly noteworthy, i.e. the reportage by Yuri Lepski Brodskiy tol’ko chto ushël (2020), which is entirely devoted to the experiences related to the journey in the footsteps of the poet and Progulki s Brodskim i tak daleye. Iosif Brodskiy v fil’me Alekseya Shishova i Yeleny Yakovich (2016) by Yelena Yakovich, where Brodsky himself interprets the title of his essay. Methodological tools deriving from the field of geopoetics and cultural geography, such as the place of imagination or reading journeys, proved helpful during the development of the paper.